RSM Based Modeling for Surface Roughness Prediction in Laser Machining - Sivarao, Subramonian; T., Joseph Sahaya Anand; Abd Rahman, Ammar; Salleh, Mohd Shukor (IJENS Publishers, 2010)
Statistics is a branch of mathematics used extensively in natural science and also in the engineering field as well as in social science, physics and computing. The machining process selected for this study is laser cutting process of mild steel. Response surface methodology will be used as a technique for the statistical study. The influence of cutting speed, frequency and duty cycle on surface roughness will be a main portion of this study. For statistical approach, a mathematical based model has been developed through regression analysis to study the response prediction. It is found that for the surface roughness, cutting speed plays an important role. Only a high cutting speed can produce good surface roughness coupled with high duty cycle regardless of frequency.